POLITIK HUKUM PERTANGGUNGJAWABAN PIDANA TERHADAP INTERNET SERVICE PROVIDER DALAM CYBER CRIME - , Alwalid Muhammad ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research studied about legal politic of criminal responsibility for internet service provider aiming to describe theoretical framework as a base of internet service provider to have criminal obligation, making explicit of the form of criminal responsibility burden to internet service provider if involved in cyber crime and finding the parameter and giving suggestion of ideal legal politic of criminal responsibility in the future as a dreamt law ( ius constituendum) in cyber world according to the requirement of technological advances and modern information. This research was a normative research supporter by data obtained in the field using research approach of legal politic used to study ius constitutum and gave thought toward ius constituendum about the criminal responsibility for internet service provider. The research result for the first problem showed that so far, the criminal responsibility for internet service provider as cooperation is still promoting sharp enough difference of idea among the experts, mainly in case of investigation, searching, and confiscation. For the second problem, in Regulation Number 11 year 2008 about he Electronic Information and Transaction in relation with the form of criminal responsibility if internet service provider is involved in cyber crime is still not arranged clearly and firmly. Besides, the problem faced by the investigators causing the internet service provider could not be obliged by responsibility because in the investigation, searching, and confiscation has to have license in its implementation from the chairman of local court or from the Minister of information and communication. Answering the third problem, Pancasila as the spirit used in legal politic in Indonesia has to be the ideology, the source of value and orientation in determining the direction of legal politic development in Indonesia. On the way of modern era, societal protection in cyber world is still weak and far from the expected one, through the product of positive law recently.